INTELLECTUAL ANALYTICAL GEOINFORMATION SYSTEM “EARTH SCIENCE DATA FOR THE TERRITORY OF RUSSIA” (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The present study is aimed at the integration of data on geography, geology, geophysics, geoecology and other Earth sciences in the comprehensive problem-oriented geoinformation system (GIS) including the intellectual superstructure for geoinformation analysis. At the present time GIS provide only limited opportunities for general analysis of geodata handled. At the same time, among the scientific community, dealing with the Earth sciences data, the requirement of more profound and comprehensive data analyzing and processing is constantly growing. The theory and methods of artificial intellect (AI) must become not only an integral, but the main core of a modern GIS. The methods of fuzzy mathematics correlate with a fuzzy character of geophysical data. The AI methods, developed by the authors, and presently applied to volcanic activity monitoring, search and interpretation of anomalies in geophysical fields, solving environmental, geodynamic and other problems, turned out to be a success.